1999
DOI: 10.1161/01.str.30.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of White Matter Damage in Ischemic Leukoaraiosis with Diffusion Tensor MRI

Abstract: Background and Purpose-Information on the neuropathological changes underlying ischemic leukoaraiosis is only available postmortem, and there are limited data on histological appearances early in the disease. Diffusion tensor imaging allows determination of the directionality of diffusion, which is greater in the direction of white matter bundles. Therefore, the technique might be expected to show loss of anisotropy (directional diffusion) in leukoaraiosis. Methods-Nine patients with ischemic leukoaraiosis (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
164
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(175 citation statements)
references
References 20 publications
9
164
1
1
Order By: Relevance
“…The mean volume ratio, 25 which characterizes anisotropy, was higher both in regions of T 2 -weighted hyperintensity (0.92 AE 0.04) and in NAWM (0.87 AE 0.07) compared with normal white matter in controls (0.68 AE 0.04). In common with the findings of Jones et al 19 in ischaemic leukoaraiosis, there was a strong correlation (r = 0.81; p = 0.0002) between mean diffusivity and anisotropy in regions of T 2 -weighted hyperintensity. In explaining the moderate increase in diffusion in NAWM and severe (60%) increase in white matter exhibiting T 2 -weighted hyperintensities, Chabriat et al suggested that the marked increase in diffusivity in regions of T 2 -weighted hyperintensity was due to neuronal loss, while the mild increase in the NAWM was due to myelin loss.…”
Section: Ischaemic Leukoaraiosissupporting
confidence: 88%
See 2 more Smart Citations
“…The mean volume ratio, 25 which characterizes anisotropy, was higher both in regions of T 2 -weighted hyperintensity (0.92 AE 0.04) and in NAWM (0.87 AE 0.07) compared with normal white matter in controls (0.68 AE 0.04). In common with the findings of Jones et al 19 in ischaemic leukoaraiosis, there was a strong correlation (r = 0.81; p = 0.0002) between mean diffusivity and anisotropy in regions of T 2 -weighted hyperintensity. In explaining the moderate increase in diffusion in NAWM and severe (60%) increase in white matter exhibiting T 2 -weighted hyperintensities, Chabriat et al suggested that the marked increase in diffusivity in regions of T 2 -weighted hyperintensity was due to neuronal loss, while the mild increase in the NAWM was due to myelin loss.…”
Section: Ischaemic Leukoaraiosissupporting
confidence: 88%
“…Jones et al 19 applied DT-MRI to a study of nine patients with ischaemic leukoaraiosis and 10 agematched controls. They defined ischaemic leukoraraiosis as the radiological appearance of diffuse periventricular white matter changes on conventional MR imaging in patients with a history of lacunar stroke and/or a subcortical dementia believed to be of vascular origin.…”
Section: Ischaemic Leukoaraiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Other clinical applications include characterization of tumors [6,7] or multiple sclerosis lesions [8][9][10] and white-matter fiber-tract imaging by determining diffusion anisotropy [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In vivo knowledge of SVD has developed largely as a result of progress in neuroimaging, which has allowed a detailed characterization and classification of anatomical and physiological changes associated with this condition. 4 As an example, recent studies using diffusion tensor imaging show an association between SVD and microstructural changes within selected white matter tracts, 5,6 changes which have been linked to gait disturbances, 7 decreased performance on cognitive testing, 8 and may precede the development of white matter lesions detected using conventional sequences such as T2 or FLAIR. 9 Despite such advances, a systems-level understanding of how SVD contributes to cognitive dysfunction is missing.…”
mentioning
confidence: 99%